Digital transformation: utilization of technologies such as Artificial Intelligence (AI), internet of things (IoT), and blockchain to increase efficiency and innovation in business - Wulandar, Novita; Septya, Ninik (2025)
Digital transformation has become a key catalyst in the evolution of modern businesses. This study examines how technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), and blockchain can be applied to enhance operational efficiency and drive innovation in business strategies. The analysis includes case studies and recent literature to identify the main benefits, challenges, and opportunities associated with the adoption of these technologies. The findings indicate that the integration of these three technologies can provide significant competitive advantages across various industrial sectors.